2014
DOI: 10.1007/s13235-014-0124-0
|View full text |Cite
|
Sign up to set email alerts
|

Lyapunov Functions for Time-Scale Dynamics on Riemannian Geometries of the Simplex

Abstract: We combine incentive, adaptive, and time-scale dynamics to study multipopulation dynamics on the simplex equipped with a large class of Riemannian metrics, simultaneously generalizing and extending many dynamics commonly studied in dynamic game theory and evolutionary dynamics. Each population has its own geometry, method of adaptation (incentive), and time-scale (discrete, continuous, and others). Using information-theoretic measures of distance we give a widely-applicable Lyapunov result for the dynamics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…It is easy to observe that mixed ESS is the unique HSO(1). In passing, we remark that the concept of incentive stable state equilibrium [22] to describe incentive dynamics is simply HSO(1). We also observe that one could in principle replace states by strategies and use appropriate payoff matrix (U, say) in Inequality (17) to analogously define heterogeneity stable strategy (HSS).…”
Section: Heterogeneity Stable Orbitmentioning
confidence: 99%
See 1 more Smart Citation
“…It is easy to observe that mixed ESS is the unique HSO(1). In passing, we remark that the concept of incentive stable state equilibrium [22] to describe incentive dynamics is simply HSO(1). We also observe that one could in principle replace states by strategies and use appropriate payoff matrix (U, say) in Inequality (17) to analogously define heterogeneity stable strategy (HSS).…”
Section: Heterogeneity Stable Orbitmentioning
confidence: 99%
“…This is the case for other monotone dynamics in evolutionary game theory as well. In literature there are many different evolutionary dynamical models: some of them can be obtained by varying revision protocol [16,17], e.g., replicator dynamics [14], best response dynamics [18], Brownvon Neumann-Nash dynamics [19], Smith dynamics [20] and logit dynamics [21]; whereas some can be seen as variants of incentive dynamics [22], e.g., replicator dynamics [14], best response dynamics [18], logit dynamics [21] and projection dynamics [23]. All the aforementioned dynamics have the common property of converging towards NE [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the product is not monotonically increasing but is still positive. Authors of [17] proved the stability of the escort evolutionary dynamics with positive monotonically increasing escort functions. Even if it is out of the scope of this paper, it is possible to prove that the following divergence-like function,…”
Section: B Stabilitymentioning
confidence: 99%
“…The Fermi process of Traulsen et al is the q-Fermi for q = 1 [25], and q = 0 is called the logit incentive, which is used in, e.g., [42]. The q-replicator incentive has previously been studied in the context of evolutionary game theory [30,33] and derives from statistical-thermodynamic and information-theoretic quantities [43]. Recently human population growth in Spain has been shown to follow patterns of exponential growth with scale-factors q = 1 [44].…”
Section: Dynamicsmentioning
confidence: 99%
“…While it is true that on the interior of the probability simply many incentives can be re-written as nonlinear fitness functions, there are significant advantages to the change in perspective from fitness-proportionate selection to incentive proportionate-reproduction. In particular, the authors showed in [33] that incentives ultimately lead to a deeper understanding of evolutionary stability and a substantial improvement in the ability to find Lyapunov functions (via formal and geometric considerations) for a wide-range of evolutionary dynamics. Moreover, when dynamics interact with the boundary, such as innovative and non-forward invariant dynamics, incentives yield a better description of evolutionary stability.…”
Section: Dynamicsmentioning
confidence: 99%